Diversifikasi Produk Olahan Pangan Hasil Aplikasi Vertikultur Tanaman Sayuran di Kelurahan Tengah, Kramat Jati, Jakarta Timur - Julfi Restu Amelia; Ira Mulyawati; Lisa Ratnasari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Utilization of garden area at this time is still not optimal, and the development of various innovations related to the garden area is also limited. This fact related with the garden that owned by the people in general is very narrow. Verticulture is one of technique that can be used for narrow land in urban farming. The target audience of the activity is the partners and the community of Kelurahan Tengah, East Jakarta. The problems that exist are decreasing in interest and participation of target audience in carrying out reforestation activities due to limited land, and in the development of processed food products that is related with the difficulty of raw materials and the limitations of product marketing. The aim of the activity is to increase the participation of target audiences through assistance in optimizing reforestation activities, processing food products and developing market systems through online marketing. The method used in the activity are approach, socialization, and training, such as training on greening technology packages (verticulture techniques); food processing training: drinks from spinach, carrot and pineapple (Batelnas), drinks from okra, honey and ginger (The Kraduu), dodol from ginger and sesame (Dojawi), and dodol from ginger and carrot (Dojawo); and digital marketing technique training. The results showed that activity through appropriate technology transfer and assistance to the target audience is able to increase interest and participation and better care for the environment as well as business opportunities from such activities. The products resulted from this activity are new innovation products so that they have economic added value, and if it continuously done, it will increase household income of the target audience.